Volunteers during a crisis in Israel: a case study of spontaneous self-organized volunteer activity - Edith Shamir-Tixell (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2022)
In Israel, a large number and a wide range of non-governmental volunteering organizations exist in various fields. At the same time, due to the multiplicity of security incidents and other national crises, there are also numerous independent volunteer initiatives emerging within specific communities, small communities, or cities. Private initiatives that started as small volunteer aid have grown mainly thanks to the technological possibilities that enable the transfer of information about a crisis and the needs associated with it. This study examines the volunteers’ perception of effectiveness in a self-organized spontaneous setting, and their sense of belonging to the community and the State of Israel. This article presents a case study of unorganized, spontaneous volunteer activity in Israel in situations of stress and crisis. The study is based on participant observation and semi-structured interviews with those who engaged in spontaneous self-organized volunteer activity. The study findings show that mobilizing volunteers through WhatsApp messages strengthened the sense of effectiveness in performing the task, fostered the volunteers’ sense of belonging to their community, and contributed to the rapid achievement of the task. The study also highlights the socio-moral dimensions that intensify in such a volunteering process and the individual’s feelings about his place in society and his observation of society’s behaviour in general.